A Bibliometric Analysis of Stakeholders' Perceptions on Public Service Quality and Performance. Trends, Themes and Future Directions - SABIE Oana-Matilda; BUNEA Ovidiu-Iulian; POPESCU Ruxandra-Irina (Applied Research in Administrative Sciences)
This article undertakes a comprehensive study of worldwide literature gathered from the Web of Science database, using bibliometric analysis. The analysis covers all the years, and most publications are from 1988 to 2024. The primary focus of the inquiry centres on the development of public service concept, public services citizens’ satisfaction, services’ stakeholders, public services’ quality and performance during this period. The assessment of public services quality by citizens has been a prominent subject of scholarly investigation for a considerable period of time. By conducting keyword co-occurrence analysis on pertinent literature, our objective was to uncover dominant themes and track trends over a period of time. Novel insights were obtained by generating density, network, and overlay maps using VOS Viewer software. The keyword co-occurrence analysis performed using VOS Viewer unveiled an intricate and interrelated network of study themes within the literature on stakeholders' perceptions of the quality and performance of public services. The study discovered four main clusters, each reflecting separate yet intersecting research topics. An in-depth analysis of these clusters provides significant insights into the emerging patterns and key areas of interest in this subject. This research provides essential insights for both academic and practical applications in public services, establishing a foundation for future investigations.